The Immunomodulatory Effects of Mesenchymal Stem Cell Polarization within the Tumor Microenvironment Niche - Cosette M. Rivera-Cruz; Joseph J. Shearer; Manoel Figueiredo Neto; Marxa L. Figueiredo (Hindawi Limited, 2017)
Mesenchymal stem cells (MSCs) represent a promising tool for cell therapy, particularly for their antitumor effects. This cell population can be isolated from multiple tissue sources and also display an innate ability to home to areas of inflammation, such as tumors. Upon entry into the tumor microenvironment niche, MSCs promote or inhibit tumor progression by various mechanisms, largely through the release of soluble factors. These factors can be immunomodulatory by activating or inhibiting both the adaptive and innate immune responses. The mechanisms by which MSCs modulate the immune response are not well understood. Because of this, the relationship between MSCs and immune cells within the tumor microenvironment niche continues to be an active area of research in order to help explain the apparent contradictory findings currently available in the literature. The ongoing research aims to enhance the potential of MSCs in future therapeutic applications.